The Effects of Tempol on Cyclophosphamide-Induced Oxidative Stress in Rat Micturition Reflexes. (20th April 2015) - Gonzalez, Eric J.; Peterson, Abbey; Malley, Susan; Daniel, Mitchel; Lambert, Daniel; Kosofsky, Michael; Vizzard, Margaret A.
Abstract : We hypothesized that cyclophosphamide- (CYP-) induced cystitis results in oxidative stress and contributes to urinary bladder dysfunction. We determined (1) the expression of oxidative stress markers 3-nitrotyrosine (3-NT), reactive oxygen species (ROS)/reactive nitrogen species (RNS), inflammatory modulators, neuropeptides calcitonin gene-related peptide (CGRP), substance P (Sub P), and adenosine triphosphate (ATP) that contribute to the inflammatory process in the urinary tract and (2) the functional role of oxidative stress in urinary bladder dysfunction with an antioxidant, Tempol, (1 mM in drinking water) combined with conscious cystometry. In CYP-treated (4 hr or 48 hr; 150 mg/kg, i.p.) rats, ROS/RNS and 3-NT significantly (P ≤ 0.01 ) increased in urinary bladder. CYP treatment increased ATP, Sub P, and CGRP expression in the urinary bladder and cystometric fluid. In CYP-treated rats, Tempol significantly (P ≤ 0.01 ) increased bladder capacity and reduced voiding frequency compared to CYP-treated rats without Tempol. Tempol significantly (P ≤ 0.01 ) reduced ATP expression, 3-NT, and ROS/RNS expression in the urinary tract of CYP-treated rats. These studies demonstrate that reducing oxidative stress in CYP-induced cystitis improves urinary bladder function and reduces markers of oxidative stress and inflammation.